Dc‐link current computational methods for three‐phase inverter with low‐order harmonic output current. Issue 4 (1st April 2019) - Wang, Tao; Lu, Shuai
Abstract : Both the spectral analysis and the closed‐form root‐mean‐square (RMS) equations are widely used to determine the three‐phase inverter dc‐link current for capacitor rating proposed. However, the analytical models of the dc‐link currents have rarely been reported for applications like the active power filter, where ac currents are mostly low‐order harmonics (LOHs). This paper first derived expressions for each dc‐link LOH current, in order to compute the capacitor losses for each LOH frequencies. Then, it is shown that the derivation of the dc‐link switching harmonic current (SHC) RMS equation is very much complicated when LOHs are present in the ac currents. Hence, new set of generalised RMS equations were successfully derived and simplified into one equation to facilitate the worst case design. The design case of the dc‐link current is demonstrated with the proposed equations. A flexible grid‐tied inverter lab prototype is developed to inject arbitrary combinations of LOH currents of different orders, sequences, amplitudes and angles into the grid. Good match between the computational and experimental results validates the proposed methods.